The Effectiveness of Cognitive-Behavioral Therapy Training on the Verbal Intelligence of Students Participating in English Language Learning Classes - Karimi Baghmalek, Ayatollah; Mahhigir, Foroogh; Riazi, Nastaran; Ghorbannejad, Moein (International Journal of Education and Cognitive Sciences, 2022)
The present study was conducted with the aim of determining the effectiveness of cognitive behavioral therapy training on the verbal intelligence of students participating in English language learning classes. The studied population consists of all students who participated in English language learning classes in Shiraz. The sampling method of the present study was the staged cluster sampling method. The current sample size was selected based on previous researches. In the current research, the cognitive-behavioral skills training package and the verbal intelligence questionnaire were used. The results showed that the verbal intelligence post-test scores in the experimental and control groups were significantly different after removing the effect of the pre-test scores, and the effect of the verbal skills training Cognitive behavior was on the increase of verbal intelligence. Other results showed that the difference between the adjusted averages of verbal intelligence of the experimental and control groups in the post-test was statistically significant. Teaching cognitive-behavioral skills helps male students to reach a level of verbal intelligence in different situations.